Pengaruh Gaya Kepemimpinan Demokratis dan Lingkungan Kerja terhadap Kinerja Karyawan pada Badan Pusat Statistik Jakarta Selatan - Wan Milanda Novita Sari; Alan Budi Kusuma (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Human resources influence the performance of a company. Therefore, so that employees understand their duties and can carry out their responsibilities well within the company, there is also a need for democratic leadership and a comfortable working environment. The method used by the author in this research is a quantitative method with a sampling technique, namely saturated samples. The data used in this research was collected by distributing questionnaires to 60 BPS employee respondents. Data processing techniques use validity test analysis, reliability test, classical assumption test using normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, hypothesis testing using t test and f test, and coefficient of determination analysis using partial and simultaneous. Based on the results of the simultaneous test, the F test is (78,670) > F table (3.16), proving that the Democratic Leadership Style and Work Environment variables together have a positive and significant influence on employee performance with the multiple linear regression equation Y = 1.851 + 0.296X1 + 0.657X2 and a coefficient of determination value of 0.734, it can be concluded that Democratic Leadership Style (X1) and Work Environment (X2) together have an influence contribution of 73.4% on Employee Performance (Y).